Chitosan-coated microvesicles: Effect of polysaccharide-phospholipid affinity on decafluorobutane dissolution. (20th November 2016) - Picheth, Guilherme F.; Pirich, Cleverton L.; dos Santos, Larissa A.; Camarozano, Ana C.; Sierakowski, Maria Rita; Ocampos, Fernanda M.; Barison, Andersson; Kaminski, Gabriel A.; Pontarolo, Roberto; de Freitas, Rilton Alves
Graphical abstract: Highlights: Chitosan-DSPC interactions are disclosed by surface-sensitive techniques. Chitosan induces more stable phospholipid organizations in microvesicles. Chitosan-coated microvesicles preserve C4 F10 for longer periods. Long-lasting ultrasonic images and enhanced shelf stability are achieved. Abstract: The stability of perfluorinated microvesicles is mainly determined by the presence of interfacial materials and their ability to hinder the gas component diffusibility into the bloodstream. The goal of this study is to increase the persistence of the gaseous-core by introducing chitosan-coated 1, 2-distearoyl-sn- glycero -3-phosphocholine (DSPC) microvesicles, reducing gas diffusion from microvesicles, and increasing for a long time ultrasonic signals. Our hypothesis was based on the irreversible adhesion of chitosan towards DSPC head groups observed in thin-films models. This affinity enhanced the stabilization of gaseous-core microvesicles, in which the polysaccharide effectively reduced the phospholipid phase transition enthalpy from 383 ± 5.5 J mg −1 for plain to 150 ± 9.7 J mg −1 for chitosan-coated microvesicles, providing a more stable structure that diminished the gaseous component lost and provided the persistence of intense 19 F-NMR signals after 48 h, twice as long compared to plain samples. As a result, stronger and long-lasting ultrasonic signals were produced by the more stable chitosan-containing microvesicles, thus, presenting great potential to increase the diagnostic and therapeutic applications of perfluorocarbon carries.